A Note on Economic Growth, Inequality, and Poverty in the Philippines - Aubrey D. Tabuga; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2011)
This paper examines the relationship among poverty, economic growth, and inequality by decomposing poverty changes at subnational levels. The results were examined against the performances of the different economic sectors in the regions to understand the relationships while accounting for the nature of growth. Moreover, the poverty elasticity of output growth was estimated using regional-level data in 2003, 2006, and 2009. We learned that while the rate of growth matters a lot in poverty reduction, the redistribution of income matters as well. More importantly, we find that, at a given rate of growth, the response of poverty rate to growth is higher when income distribution is less unequal.
Keywords: 330; poverty; decomposition; inequality; Philippines; GLS regression; random effects; Gini decomposition; Armut; Wirtschaftswachstum; Verteilungswirkung; Soziale Ungleichheit; Gini-Koeffizient; Philippinen